Improving turn-around times in low-throughput distributed hematology laboratory settings with the CellaVision® DC-1 instrument - Mayes, Cheri; Gwilliam, Tracey; Mahe, Etienne R. (Journal of laboratory medicine, 2025)
Digital pathology is becoming standard in the delivery of timely, high-quality clinical services, inclusive of morphological assessment in laboratory hematology. While many digital hematology systems are designed with high-throughput in mind, CellaVision® has recently developed a low-throughput instrument, the CellaVision® DC-1. The utility of the CellaVision® DC-1 was tested in a distributed laboratory system, with a focus on turn-around times (TATs).